Host Differentiation and Compartmentalization of Microbial Communities in the Azooxanthellate Cupcorals Tubastrea coccinea and Rhizopsammia goesi in the Caribbean - Engelen, Aschwin H.; Aires, Tânia; Vermeij, Mark J. A.; Herndl, Gerhard J.; Serrão, Ester A.; Frade, Pedro R. (Frontiers in Marine Science, 2018)
We investigated the microbial communities associated with surface layer mucus, tissue and gastrovascular cavity of two azooxanthellate Caribbean cup corals (Tubastrea coccinea and Rhizopsammia goesi) to explore potential differences in microbial community composition within and among these azooxanthellate scleractinian corals. Using next-generation sequencing of the V3-V6 region of the 16S rRNA gene we found that while alpha-diversity was overall very similar, the relative abundance of microbial taxa differed between host species and among locations within a polyp (i.e., compartments). The distinct microbial assemblages between species is only challenged by the relatively high similarity among mucus samples of both species. This suggests a stronger signal of the surrounding environment and weaker host control over the mucus compartment compared with the tissue and gastrovascular cavity. Tubastrea coccinea harboured four indicator OTUs (including a Pseudoalteromonas species, an unidentified Gammaproteobacteria, an unidentified OTU in the family Comamonadaceae and one in the genus Burkholderia). The single indicator for R. goesi was another undetermined OTU in the Comamonadaceae. The microbial communities of the gastrovascular cavity and the mucus overlapped substantially in indicator OTUs. None of these were exclusive of the gastrovascular cavity or mucus, while an OTU of the order Thiohalorhabdales occurred uniquely in the tissue. In contrast to the gastrovascular cavity and mucus, the tissue of both coral species was rich in chloroplasts of different algal taxa (mainly Ulvophyceae and Stramenopiles), and an OTU of the genus Roseivirga (family Flammeovirgaceae). The two coral species shared most indicator OTUs for microbial communities residing in their mucus and tissue, but not in their gastrovascular cavities. However, Endozoicomonadaceae occurred in the tissue of both coral species. The genus Pseudomonas was found in R. goesi but was virtually absent in T. coccinea. This study demonstrates the influence of coral compartments and species identities on the composition of microbial communities associated with azooxanthellate cup corals and emphasizes the important effects of within-polyp microhabitats in structuring the coral microbiome.